Health Education Based On Social Media (WhatsApp) Towards Knowledge And Attitude Of The Prospective Bride About Reproductive And Sexual Health - Hani Sutianingsih; Rery Kurniawati; Tutik Iswanti (POLTEKKES KEMENKES PONTIANAK, 2021)
Women are more vulnerable to reproductive health risks, including sexually transmitted infections, verbal abuse, and physical violence. Good knowledge and attitude regarding gender equality before starting a marriage is vital so that the two brides and grooms are mutually responsible for ensuring the safety and security of the bride and groom. Online social media is designed to facilitate interactive social interactions based on internet technology. Whatsapp is the most popular chat application for Indonesians. This is an opportunity when used for learning activities because WhatsApp can convey messages in text, images, sounds, and videos to deliver news about sexual and reproductive health that can be more relevant. The subject of this research is the bride and groom at KUA Cibadak Kab. Lebak, Banten Province. The design of this research is pre-post with control group design. The control group was given lectures on sexual and reproductive health, and the treatment group was assigned health education through social media WhatsApp with 15 people in each group. Based on the results of statistical tests, it was found that there was an effect of WhatsApp social media health education on the knowledge and attitudes of the bride and groom about sexual and reproductive health with a p-value of 0.001. WhatsApp social media can be used as a medium for reproductive and sexual health education for brides and grooms.